KEARIFAN LOKAL DALAM PEMBELAJARAN MATEMATIKA UNTUK MEMBENTUK KARAKTER SISWA DI SMPN 3 KURIPAN - Martoni Yuda Pratama; Khairil Anwar (STKIP Subang, 2024)
The background of this research is that learning mathematics is often cobsidered a difficult subject for students, so that this results in students being lazy to learn mathematics. The purpose of this research is to analyze and describe local wisdom in learning mathematics to form siews character at SMPN 3 Kuripan. This study used the library research method, namely the library method which was carried out to collect data related to previous research, while it was carried out by taking samples of learning practices at schools where the researcher became a mathematics teacher at SMPN 3 Koripan. Based on the results of the study, there were several mathematical concepts that based on local wisdom which includes the traditional bangman form of the Saxak tribe, the Sak kingdom, and Sasak pocket arts. There is a term for dividing the inheritance of suks sasak